NURSING AND ANAESTHESIA: HISTORICAL DEVELOPMENTS IN CANADA - Dunlop, Jennifer; Boschma, Geertje; Jefferson, Rosella (Operating Room Nurses Association of Canada Journal, 2009)
There is little historical knowledge available about nurses’ role in anaesthesia in Canada. It appears, from the few sources available, that nurses did administer anaesthesia in the early 20th century in Canada. The limited historiography reveals that nurses who worked in small rural hospitals across Canada were, due to the lack of physician specialty and coverage, involved in the administration of anaesthesia. To learn more about nurses’ role in this area the authors explored the oral history collection from the British Columbia’s History of Nursing group at the College of Registered Nurses of British Columbia Library. Several stories indicated that between 1917 and 1953 there were opportunities for Canadian nurses to administer anaesthesia. The oral histories identified that there was a need for the administration of anaesthesia, that nurses had the skill to provide it, and that flexibility in their nursing practice enabled them to fulfill this role. There was an increasing need for anaesthesia service that was not being filled by physicians. To further explore nurses’ role the authors also examined nursing and medical journals from that time period. There is limited understanding of how this role ceased to exist in Canada while it became well established in the United States. Various legal cases from that time period, and the substantially different results between Canadian and America cases, provide some insight into the reasons why nurse anaesthetists were excluded from anaesthesia practice in Canada. As the Canadian healthcare environment continues to change, and the need for anaesthesia services increases, new questions have begun to arise about the potential for an advanced practice role in anaesthesia for Canadian nurses. The demand for anaesthesia services is increasing in-line with the aging Canadian population and the shortage of available services is most dramatic in small, rural hospitals. This article provides important historical background on the development of the role of nurse anaesthetists in Canada.